2019
DOI: 10.1055/s-0039-1695718
|View full text |Cite
|
Sign up to set email alerts
|

The Differing Effect of Gender and Clinical Specialty on Physicians' Intention to Use Electronic Medical Record

Abstract: Background The use of electronic medical record (EMR) is anticipated to bring benefits for patients, physicians, and organizations. But limited physicians' acceptance of EMR presents a serious threat to its effective implementation. Objectives The current study incorporates technology acceptance model (TAM) with two antecedents, gender, and clinical specialty and one context-specific factor, financial incentives, to identify the factors that influence physicians' intention to use EMR in Taiwan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 88 publications
0
6
0
5
Order By: Relevance
“…Three experts have received their Ph.D. degrees already, and another one will receive her Ph.D. degree shortly. The age distribution of the experts was between 40-52 years (3 of them belong to the 40-50 group and 1 belongs to [45][46][47][48][49][50]. A significant concern to ask those experts to serve as the panel members is their expertise areas that are much more related to information science.…”
Section: The Delphi Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three experts have received their Ph.D. degrees already, and another one will receive her Ph.D. degree shortly. The age distribution of the experts was between 40-52 years (3 of them belong to the 40-50 group and 1 belongs to [45][46][47][48][49][50]. A significant concern to ask those experts to serve as the panel members is their expertise areas that are much more related to information science.…”
Section: The Delphi Methodsmentioning
confidence: 99%
“…A positive attitude refers to the individual's perception of a specific behavior. Previous studies validated that citizens observe guidelines, necessities, and strategies while having a positive attitude [13,48,49,58]. On the other hand, infodemics negatively influence citizens' attitude, influencing them to give away a specific behavior.…”
Section: Moderating Effect Of Health Infodemicmentioning
confidence: 96%
See 1 more Smart Citation
“…When reviewing the predictor variables of behavioral intention to use, in the cases under study, considerable heterogeneity was observed. Some studies found only 1 primary variable from TAM, such as perceived usefulness or perceived ease of use, associated with intention to use [30,31], and other studies reported subjective norm or job relevance directly related to behavioral intention to use, without being intermediated by perceived usefulness [30][31][32]. There are also studies that describe predictors of perceived ease of use, such as job relevance, management support, and training or computational self-efficacy [33,34], and some others found that age, sex, or clinical specialty were predictors of both perceived usefulness and perceived ease of use [31].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Some studies found only 1 primary variable from TAM, such as perceived usefulness or perceived ease of use, associated with intention to use [30,31], and other studies reported subjective norm or job relevance directly related to behavioral intention to use, without being intermediated by perceived usefulness [30][31][32]. There are also studies that describe predictors of perceived ease of use, such as job relevance, management support, and training or computational self-efficacy [33,34], and some others found that age, sex, or clinical specialty were predictors of both perceived usefulness and perceived ease of use [31]. This variability supports the idea of contextualizing the results of each study not only referring to the type of technology used but also to the organizational culture in which the technology will work.…”
Section: Comparison With Prior Workmentioning
confidence: 99%